Visualisasi Hasil Produksi Pangan di Provinsi Nusa Tenggara Timur - Abineno, Richard Sanni; Mamulak, Natalia Magdalena R.; SinlaE, Alfry Aristo Jansen (LPPM UNIKA Santo Thomas Medan, 2019)
The Department of Agriculture of the Province of East Nusa Tenggara (NTT) is a regional apparatus with the main task of providing services to the community in the agricultural sector, one of which is food coverage. The website http://distan.nttprov.go.id does not yet contain information about food production results that are complete and clear. To overcome these problems, it is necessary to build a Food Production Results Visualization which is expected to display a picture of food production results based on the year of production, types of commodities and production results from each district in the province of East Nusa Tenggara that is easily accessed and understood by the public. The method used in this study is the waterfall system development method. The graphic design displayed on this website uses ChartJS. The programming languages used are PHP 7 and MySQL as database server. The results of this study are a Web-based Visualization of Food Production Results in East Nusa Tenggara Province which contains complete and clear information and is easily accessible to all parties..